Lesions misdiagnosed as endodontic pathosis: A narrative review - Amit Hemraj Patil; Shruti Singh; Aarti S Bedia; Deepak Sharma; Anamika Sinha; Nitesh Dahiya (Journal of Pharmacy and Bioallied Sciences, 2024)
In daily practice, clinicians come across certain radiographic abnormalities which may or may not be asymptomatic. This abstract discusses radiographic abnormalities encountered by clinicians in daily practice, some of which resemble endodontic lesions. Prompt attention is crucial as these lesions can be benign or malignant. The article emphasizes the importance of differential diagnosis for accurate identification of periapical pathosis.